Relationship between personality, mindset, academic motivation on grit (persistence) in middle school students - Aulia, Fitri; Takiuddin, Muhammad; Rahmatullah, Abdul Halim (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
This study aimed to determine the relationship between personality, mindset, and academic motivation of Grit students in high school. Who used the ex post facto quantitative method with simple random sampling to take a sample of 80. The instrument has four variables: personality, mindset, academic motivation, and Grit. The data analysis technique used multiple regression analysis. The results of the hypothesis show that the personality variable with t count > t table is (3.123 > 1.996), mindset variable with t count > t table (2.208 > 1.996) and academic motivation variable with t count > t - table (11.02 > 1,996). These data indicate that overall, all Ho is rejected, and Ha is accepted of the three variables. Based on the Simultaneous test results (F test), the significance value of the personality, mindset, and academic motivation variables is smaller than the significance value of 0.000 <0.05. So we can conclude that the variables of personality, mindset, and academic motivation simultaneously have a relationship with Grit in high school students.